2013
DOI: 10.1016/j.neunet.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficient online bootstrapping of sensory representations

Abstract: This is a simulation-based contribution exploring a novel approach to the open-ended formation of multimodal representations in autonomous agents. In particular, we address the issue of transferring ("bootstrapping") feature selectivities between two modalities, from a previously learned or innate reference representation to a new induced representation. We demonstrate the potential of this algorithm by several experiments with synthetic inputs modeled after a robotics scenario where multimodal object represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In previous articles [18], [19], PROPRE was already applied on artificial data representative of a robotic task. In this article, targeting the use of PROPRE on real robotic platform, we illustrate multiple of its functional properties when applied to real visual pedestrian data on a challenging supervised classification task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous articles [18], [19], PROPRE was already applied on artificial data representative of a robotic task. In this article, targeting the use of PROPRE on real robotic platform, we illustrate multiple of its functional properties when applied to real visual pedestrian data on a challenging supervised classification task.…”
Section: Discussionmentioning
confidence: 99%
“…We previously studied the PROPRE paradigm with artificial multimodal data related to basic robotic behaviors [18], [19]. Targeting its use on a real developmental robotic platform, in this article we apply it to a challenging visual discrimination task of namely real-world pedestrian pose classification [20], [21] (see figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The first of the aforementioned explanations is however unlikely, because the correlation of El-Shanawany yields relatively small droplet sizes compared to those obtained using other empirical correlations for prefilming airblast atomizers [25,26]. The droplet life time is highly sensitive to the initial droplet size, so the use of a different SMD correlation will generally increase the impingement of droplets significantly.…”
Section: Droplet Evaporationmentioning
confidence: 98%
“…Regarding the second explanation, Gepperth et al [26] have shown that the droplet sizes predicted by Eq. (3) can only be representative after secondary breakup.…”
Section: Droplet Evaporationmentioning
confidence: 99%
“…Such concepts must be statistically related across sensory modalities while being non-redundant within their own modality. For achieving this in an online learning process, we propose a variant of the PROPRE (projection-prediction) algorithm [11]: PROPRE is a neural learning method which uses projection to map input stimuli to a two-dimensional neural representation ("induced representation") while using prediction from another neural representation ("reference representation") to modulate the adaptation of the projection step 1 . This results in selectivity to distinct patterns whose presence can be inferred from activity in the reference representation.…”
Section: Introductionmentioning
confidence: 99%